2018
DOI: 10.1093/advances/nmy039
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Consideration of Values When Setting Priorities in Nutrition Research: Guidance for Transparency

Abstract: Nutrition research can guide interventions to tackle the burden of diet-related diseases. Setting priorities in nutrition research, however, requires the engagement of various stakeholders with diverse insights. Consideration of what matters most in research from a scientific, social, and ethical perspective is therefore not an automatic process. Systematic ways to explicitly define and consider relevant values are largely lacking. Here, we review existing nutrition research priority-setting exercises, analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…We have used the twenty-seven nutrition priority setting papers previously identified in a systematic mapping review (5). The mapping review was updated in 2019 and one extra priority setting exercise was added in 2018 (6) (see supplementary table 1).…”
Section: Priority Setting Exercise Mapping Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used the twenty-seven nutrition priority setting papers previously identified in a systematic mapping review (5). The mapping review was updated in 2019 and one extra priority setting exercise was added in 2018 (6) (see supplementary table 1).…”
Section: Priority Setting Exercise Mapping Reviewmentioning
confidence: 99%
“…A review of nutrition priority setting exercises in 2016 summarized the main characteristics of these exercises including the priority setting objective, who is represented and the number of experts represented, target audience, funding source and follow up of results (5). The review found that 27 priority setting exercises were conducted between 1994 and 2018 covering numerous nutritional problems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are ample initiatives that have documented priorities for nutrition research or proposed a formal nutrition research agenda. A recent scoping review identified twenty-seven reported nutrition research priority setting exercises in 2018 ( 18 ) . As an example, Haddad et al .…”
Section: Stage One: Research Priority Settingmentioning
confidence: 99%
“…Moreover, values that underpin decisions for specific priorities are poorly reported in nutrition priority setting efforts. In accordance with the development of the Research Fairness Initiative to foster fair and responsible actions within global joint research and advances in health ( 38 ) , a tool was developed to ensure transparency and consideration of values when setting research priorities in nutrition ( 18 ) , which is required to be tested and monitored in the years to come.…”
Section: Stage One: Research Priority Settingmentioning
confidence: 99%
See 1 more Smart Citation